Do oil price fluctuations influence criminal activity in energy rich regions?: evidence from California’s Central Valley - Michieka, Nyakundi M. (Crime, law and social change, 2023)
This paper investigates whether shocks in oil prices affect the level of crime in Kern County, California’s top oil producing county. Monthly data from 2003 to 2018 is employed using a nonlinear autoregressive distributed lag model to test the asymmetric effects of these changes. Results for Kern County indicate that in the long-run, a negative shock in oil prices increases criminal activity while short-run oil price changes have no effect on criminal activity. Results from neighboring counties indicate that positive shocks to oil prices increase criminal activity in wealthy regions. Findings from generalized impulse response functions indicate that criminal activity in Los Angeles, Kings and San Bernardino Counties respond to shocks from Kern County’s crime rates. They also indicate that criminal activity in Inyo and Los Angeles Counties influence Kern County’s crime rate.